Understanding primary care diagnosis and management of sleep disturbance for people with dementia or mild cognitive impairment: a realist review protocol. Issue 11 (18th November 2022) - Greene, Leanne; Aryankhesal, Aidin; Megson, Molly; Blake, Jessica; Wong, Geoff; Briscoe, Simon; Hilton, Andrea; Killett, Anne; Reeve, Joanne; Allan, Louise; Ballard, Clive; Broomfield, Niall; et al.
Abstract : Introduction: The increasingly ageing population is associated with greater numbers of people living with dementia (PLwD) and mild cognitive impairment (MCI). There are an estimated 55 million PLwD and approximately 6% of people over 60 years of age are living with MCI, with the figure rising to 25% for those aged between 80 and 84 years. Sleep disturbances are common for this population, but there is currently no standardised approach within UK primary care to manage this. Coined as a 'wicked design problem', sleep disturbances in this population are complex, with interventions supporting best management in context. Methods and analysis: The aim of this realist review is to deepen our understanding of what is considered 'sleep disturbance' in PLwD or MCI within primary care. Specifically, we endeavour to better understand how sleep disturbance is assessed, diagnosed and managed. To co-produce this protocol and review, we have recruited a stakeholder group comprising individuals with lived experience of dementia or MCI, primary healthcare staff and sleep experts. This review will be conducted in line with Pawson's five stages including the development of our initial programme theory, literature searches and the refinement of theory. The Realist and Meta-narrative Evidence Syntheses: Evolving Standards (RAMESES) quality and reporting standards will also be followed. The realist review will be an iterative process and our initial realist programme theory will be tested and refined in response to our data searches and stakeholder discussions. Ethics and dissemination: Ethical approval is not required for this review. We will follow the RAMESES standards to ensure we produce a complete and transparent report. Our final programme theory will help us to devise a tailored sleep management tool for primary healthcare professionals, PLwD and their carers. Our dissemination strategy will include lay summaries via email and our research website, peer-reviewed publications and social media posts. PROSPERO registration number: CRD42022304679.